Pemanfaatan Ekstrak Kubis Ungu sebagai Media Edukasi Deteksi Hidrokuinon dalam Kegiatan Sosialisasi Kosmetik Aman untuk SISWA SMP - Widianti, Riskia Chandra; Pratiwi, Yussi; Syaadah, Rika Siti; Nurhaliza, Arinda Putri; Afianto, Riky; Mulyanah, Annisa (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: The increasing use of skin-whitening creams among adolescents has raised concerns since some products still contain hydroquinone, a hazardous chemical that has been banned by the Indonesian Food and Drug Authority (BPOM). The lack of students’ knowledge about the dangers of hydroquinone and their limited skills in detecting its presence highlight the need for practical educational activities. This community service program aimed to enhance junior high school students’ understanding of hydroquinone hazards and to provide simple detection skills using purple cabbage (Brassica oleracea var. capitata L.) extract as a natural indicator. Methods: The activity was carried out in several stages, including preparation, counseling, demonstration of hydroquinone detection with natural indicators, a question-and-answer session, and evaluation using questionnaires. Results: Evaluation showed that the majority of students responded positively, with most answers falling into the agree and strongly agree categories. This indicates an increase in students’ knowledge about the dangers of hydroquinone, their understanding of simple detection methods, and their awareness to be more selective in choosing cosmetic products Conclusions: The socialization and demonstration activities successfully provided educational benefits, trained students’ basic skills, and supported efforts to prevent the use of hazardous cosmetics. This program is also aligned with the Sustainable Development Goals (SDGs) 12 on responsible consumption and production.